Tecnologias de produção e controle de qualidade da matéria-prima vegetal, obtida a partir das folhas de Poincianella pyramidalis (TUL.) L. P. QUEIROZ - Oliveira, Agna Hélia de (2017)
Poincianella pyramidalis (Tul.) L. P. QUEIROZ is an endemic species of the caatinga biome, popularly known as "catingueira". Used in traditional medicine for the treatment of gastritis, colic, diarrhea, asthma, bronchitis, diabetes, inflammation, besides presenting cicatrizant activity. Due to this variety of medicinal uses, the species has great potential for the development of a herbal medicine. The present work had as main objectives, to standardize dry extracts, obtained by the sprinkling process, to develop and validate analytical methodology by HPLC for quantification of canferol and quercetin and to carry out an accelerated stability study of binary mixtures of dry extract with different pharmaceutical excipients. Dry extracts were obtained by spraying in Mini Spray Dryer, LabPlant, SD-05, employing the following operating parameters: air inlet temperature (160, 170 and 180 ° C), feed flow rate (4, 6 and 8 mL / min) and drying adjuvant ratio colloidal silicon dioxide (10, 15 and 20%). A 23+1 factorial design associated with MSR was applied to evaluate the effects of the process parameters on canferol and quercetin contents and to define the best operating conditions (T = 160ºC, TF = 4mL / min and% of drying adjuvant = 10 %). The simultaneous quantification of the two flavonoids was performed by HPLC in the following chromatographic conditions: ? = 370 nm, methanol: 1% phosphoric acid (47:53 v / v), pH = 3.1, 1.2 mL flow / min and Phenomenex® C18 column (250 mm x 4.6 mm x 5µ). The accelerated stability study of the binary mixtures (1: 1) of the dry extract with microcrystalline cellulose, maltodextrin, starch and lactose was carried out in a B.O.D incubator under temperature control for 180 days at a temperature of 40 ± 2 ° C. The results obtained showed that the levels of canferol and quercetin were significantly affected by the process conditions. The analytical method was linear in the range of 0.4-7.6 µg / mL for both analytes, R2 = 0.9999 and 0.9996, for canferol and quercetin, respectively. The biomarkers presented better stability in the mixtures with starch and different degradation kinetics for each excipient studied.